Percutaneous coronary intervention : ACC/AHA pocket guideline : based on the ACC/AHA/SCAI 2005 : guideline update - Smith, Sidney C., jr; Feldman, Ted E.; Hirshfeld, John W., jr; Jacobs, Alice K.; Kern, Morton J.; King, Spencer B., III, 1937-; Morrison, Douglass A.; O'Neill, William W.; Schaff, Hartzell V.; Whitlow, Patrick L.; Willams, David O. (s.n., 2005)
The American College of Cardiology (ACC) / American Heart Association (AHA) practice guidelines are intended to assist healthcare providers in clinical decision making by describing a range of generally acceptable approaches for the diagnosis, management, or prevention of specific diseases or conditions. These percutaneous coronary intervention (PCI) guidelines attempt to define practices that meet the needs of most patients in most circumstances. The guideline recommendations reflect a consensus of expert opinion after a thorough review of the available, current scientific evidence and are intended to improve patient care. If these guidelines are used as the basis for regulatory/payer decisions, the ultimate goal is quality of care and serving the patient's best interests. The ultimate judgment regarding care of a particular patient must be made by the healthcare provider and patient in light of all of the circumstances presented by that patient.